Rheological characterization of prickly pear juice (Opuntia Ficus Indica) - Marín-Machuca, Olegario; Díaz-Cachay, Catalina Beatriz; Candela-Díaz, José Eduardo; Chinchay-Barragán, Carlos Enrique; Rojas-Rueda, María del Pilar; Zambrano-Cabanilllas, Abel Walter (Edelweiss Applied Science and Technology, 2025)
The quality factors of prickly pear juice (Opuntia ficus indica), such as the flow index, consistency index, and yield stress index, proved to be important in the rheological characterization and acceptance of this food; reducing the challenges for technologies related to this product. The objectives were to characterize the rheology of prickly pear juice, determine the flow index, yield stress threshold, consistency index (K) and Pearson regression coefficients (r) and determination (r² × 100) for a temperature of 20 °C and concentrations of 5, 15, 25, and 40 °Brix. The methodology was based on the rheology of natural prickly pear juice, red-violet variety, mixed with 25% cold boiled water (p/p), with a pH of 3.64 and acidity of 0.85%. Measurements were carried out using a concentric cylinder viscometer, with a thermostatic bath for temperature control within a 0.5 °C range, from 15 °C to 70 °C, obtaining the shear stress (τ) corresponding to the strain rate gradients (γ). To determine the yield stress (τ₀) of the Herschel-Buckley rheological model (τ = K * γⁿ + τ₀), the procedure followed the theory of Bronshtein, et al. [1]. The flow index (n) and yield stress (τ₀) for prickly pear juice at concentrations of 5, 15, 25, and 40 °Brix were 0.5826, 0.7302, 0.7901, and 0.8611; and 58.0935, 65.2047, 73.3424, and 94.2155, respectively, which were progressive and directly proportional to the concentrations; concluding that the consistency index decreases and increases within the working concentration range, while the yield stress and flow index increase, and the regression (r) and determination (r² × 100) coefficients show a perfect correlation between shear stress (τ) and strain rate gradient (γ).